PERANCANGAN AUGMENTED REALITY SEBAGAI ALAT BANTU EDUKASI PELAJARAN SEJARAH DI INDONESIA BAGI SISWA SMP - VARIAN DINE MEJIRO; PETER RHIAN GUNAWAN; ELIZABETH WIANTO (Serat Rupa: Journal of Design, 2018)
History is a compulsory subject in the formal school curriculum in Indonesia. Through history lessons, students can understand and know the existence of events that eventually can foster cultural values and become the foundation of the progress of a nation. Moreover, Indonesia is a country that has a long history, one of the topics are about kingdoms that once grow and develop in the territory of Indonesia. Unfortunately, history lessons are unfavored by most junior high school students, because of their monotonous methods. Therefore, the purpose of this design is to create an interactive media for learning history in Junior High School, which until now still using teacher center learning method. Technological advances and changes in children's habits in understanding something by playing became the foundation of the concept of making history game. Interactive media created is a board game combined with Augmented Reality technology to add immersion in the game. Augmented Reality can provide experience in playing so that students can feel a real impression in the game. In addition to the game board as the primary media, used as well as media campaigns supporting the form of x-banner, advertising on social media such as Facebook and Instagram. Through the board games, students are expected to better understand the learning of the Hindu Buddhist Kingdom in Indonesia and not feel bored while studying.